An appraisal of the community development program in South Vietnam (since March 1957) - Hoang-Ngoc-Thank 1926-
In Vietnam, a community development program was organized in March, 1957. It was the purpose of this study to make an appraisal of the movement based on its principles, goals, organization and operation.